Loser Nanotechnology - Still Waiting for Nanotube Memory Chip. - Ross, P.E.
Nantero's alternative to flash memory has reached its sell-by date. Nantero's technology, based on carbon nanotubes, seemed to be the opening salvo in the nano-technology revolution. Nanotechnology nanotube-based nonvolatile memory chip is developed.
Keywords: NRAM; Nantero's technology; Carbon nanotubes; Nanotechnology; Nanotube memory chip; Nonvolatile memory chip